Peran Media Sosial Instagram Dalam Kegiatan Penjualan Produk Minuman Di Kafe Kopilikasi Pangeran Jayakarta Bekasi - Rahmi Yuniar; Akhmad Syafrudin Syahri (CV. ITTC INDONESIA, 2024)
Currently, Instagram social media plays an important role as a social media platform and has become a means of marketing communication for companies. Specifically for coffee shop businesses such as Kopilikasi, the research entitled